Frequência de ocorrência e fatores associados à hipertensão arterial em pacientes do Sistema Único de Saúde - Turi, Bruna Camilo [UNESP]; Codogno, Jamile Sanches [UNESP]; Fernandes, Rômulo Araújo [UNESP]; Monteiro, Henrique Luiz [UNESP] (My University, 2013)
Introduction: Occupying the top position among the cardiovascular diseases, hypertension accounts for about 300,000 deaths / year and, with smoking, it is the leading cause of mortality in the world population. The scientific literature shows strong evidence that the increase in the prevalence of the disease increases the costs of public health. Objectives: To verify the occurrence of hypertension in adult users of public health system and to evaluate the association between the disease and its associated factors in this population. Methods: The investigation was conducted in five Basic Health Units in the city of Bauru / SP, and consisted of 964 patients. Data from current physical activities, education, purchasing power, family history, weight, height and waist circumference (WC) were collected. Results: The occurrence of hypertension was 76.8%. Significant associations were found between the occurrence of hypertension and age, high body mass index, altered WC, sedentary lifestyle and positive family history for the disease. Conclusion: It was observed a high rate of hypertension among the evaluated subjects. Older individuals and those with hypertensive parents were the most affected by the disease. Alterations in the nutritional status indexes were positively associated with the presence of the disease and, on contrary, the practice of regular physical activity proved to be a protective factor.

Introdução: Ocupando a primeira posição entre as doenças cardiovasculares, a hipertensão arterial (HA) responde por cerca de 300 mil óbitos/ano e, juntamente com o tabagismo, é a principal causa de mortalidade da população mundial. A literatura cientifica trás fortes evidências de que o aumento da prevalência desta doença leva ao incremento nos gastos com saúde. Objetivos: Verificar a ocorrência de hipertensão arterial (HA) em adultos usuários da rede pública de saúde e avaliar a relação da doença com seus fatores associados nessa população. Métodos: A investigação foi realizada junto a cinco Unidades Básicas de Saúde, na cidade de Bauru/SP e foi composta por 964 pacientes. Foram coletados dados de atividades físicas habituais, escolaridade, poder aquisitivo, histórico familiar, peso, estatura e circunferência de cintura (CC). Resultados: A ocorrência de HA foi de 76,8%. Foram encontradas associações significativas entre ocorrência de HA e idade, índice de massa corporal elevado, CC alterada, sedentarismo e histórico familiar positivo para a doença. Conclusão: Foi observada alta ocorrência de HA entre os avaliados, sendo os indivíduos mais velhos e com pais hipertensos os mais acometidos pela doença. Alterações nos valores dos indicadores de estado nutricional se associaram positivamente à presença da doença e, em contrapartida, a prática regular de atividades físicas demonstrou ser fator de proteção.
Frequency and associated factors of hypertension in public health system patients
Keywords: Motor activity; Obesity; Hypertension; Chronic disease; Risk factors; Genetics; Atividade motora; Obesidade; Hipertensão; Doença crônica; Fatores de risco; Hereditariedade